Utilização de conhecimento de senso comum no planejamento de ações de aprendizado apoiado por computador - Carvalho, Aparecido Fabiano Pinatti de (2007)
Common sense and learning. How can this kind of knowledge, which refers to the knowledge shared by the majority of people who are inserted into the same social and cultural context, support teachers to plan learning activities which fit to pedagogical issues, important to an effective learning? How can computational technologies make viable the use of this kind of knowledge by teachers, supporting them to make decisions during the planning of tasks of a specific learning activity? This research answers these questions (i) evaluating how common sense knowledge is related to Learning Theories, proposed by Paulo Freire, Célestin Freinet, David Ausubel and Robert Gagné, authors who are renowned in the pedagogical area; (ii) exploring how computational technologies can be used to collect and present this kind of knowledge to teachers; (iii) suggesting ways to teachers use it, in order to reach pedagogical issues; and (iv) showing the use of a framework to plan learning activity, considering the suggestions of using common sense to plan learning activities, made in this research. The suggestions can be summarized in supporting teachers: (a) to decide the detail level of the learning activity topics, based on the knowledge that the target group demonstrates to have well formalized, as well as on the misunderstandings that it makes about other topics, and on the information that it forgets to mention in the knowledge base; (b) to identify topics of general interest to be taught; (c) to identify a common vocabulary used by the target group; and (d) to support the use of cognitive operators. For this purpose, it is used computational resources, developed in the context of Artificial Intelligence researches, to plan a learning activity in the in the health domain, specifically in the domain of home caring a sick person. Teachers from the Nursing Department of the Federal University of São Carlos use these resources to plan a learning activity, taking into account the common sense knowledge acquired from the Brazilian population, stored in the knowledge base of the Brazilian Open Mind Common Sense Project, developed by the Advanced Interaction Laboratory from the Computer Department of the same University in partnership with the Media Laboratory of the Massachusetts Institute of Technology. The learning activity main goal is to prepare Nursing learners to interact with the population, from which the knowledge was acquired, orienting people from that population about the procedures that might be taken, in order to home care a sick person. The results obtained are critically analyzed and they point to the validity of the suggestions of using common sense to plan learning activities made in this research